Police confirmation of use of force in Australia: "To be or not to be?" - Baker, David (Crime, law and social change, 2009)
Despite significant transgressions during encounters with Indigenous peoples and marginalised groups, all six state police organisations in Australia espouse the principle of minimum force and identify service and crime prevention as paramount in community interaction and intervention. This article offers some insight and perspective of police talk and thinking about the potential use or avoidance of force. The four Victoria Police focus groups, when confronted by the specific police use of force scenario, speak of the adrenalin rush and the need to achieve results, if reasonable and necessary by force, but also of the desire to control the situation and follow proper police procedures. Officers support ‘Safety First’ principles that advocate a cautionary and suspicious approach to the scenario combined with rational and methodical tactics rather than emotional responses. The reflective talk of individual officers about the hypothetical situation parallels actual behaviour when police collectively and visibly confront public disorder. Control and containment of the situation - whether the scenario or a major crowd disturbance - are paramount while time, in the form of acting slowly and adopting a low-key approach, can be seen as assets in achieving objectives. In both the scenario and police planning for collective action, a readiness to threaten force, rather than actually employ it, appears central to police thinking. Police justification of non-coercive tactics in certain situations can be revealing about their thinking processes in justifying force in other circumstances.